Integrating Digital Games into Project-Based Learning to Enhance Student Achievement in STEM Education - Fatma Sukmawati; Taufiq Subhanul Qodr; Theogene Rutambuka (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This study aimed to address the gap in STEM education by developing and evaluating a digital game focused on energy concepts to enhance students' learning outcomes, engagement, and collaboration. Method: The research utilized a Research and Development (R&D) approach based on the Borg and Gall model, encompassing analysis, development, validation, and implementation phases. The experimental design involved high school students divided into two groups: the experimental group, which engaged with the digital game, and the control group, which participated in conventional Project-Based Learning (PjBL) activities. Results: The findings revealed that the experimental group demonstrated significantly more improvement in STEM learning outcomes than the control group. The experimental group also showed enhanced engagement and collaboration during learning activities. Statistical analyses confirmed that the digital game effectively created interactive and engaging learning environments that fostered active participation and teamwork. Novelty: This study contributes to the field by highlighting the transformative potential of digital game-based learning to address limitations in current PjBL practices. The digital game provides a more engaging and collaborative approach to STEM education, bridging the gap between theoretical concepts and practical problem-solving.